LAYANAN BIMBINGAN KELOMPOK DALAM MEREDUKSI PERILAKU KONSUMTIF BERBELANJA PADA SISWA SMA - Dila Septiani; Putri Azzahra; Annisa Rizki Utami; Nahdhatun Nissa (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2022)
Consumptive behavior is an act of overgiving goods that do not see the need and are only for desire. This consumptive behavior is common among teenagers including high school students. Where this consumptive behavior is prone to occur and for students who have a place to live in the city area because it has been confirmed by all facilities such as malls, restaurants, cafes, apartments, hotels, and other facilities that are not far from home so that everyone can reach. Meanwhile, the distance of schools located in the pot area and close to the shopping center can lead to consumptive behavior. Consumptive behavior also has an adverse effect if the perpetrator behaves continuously. Therefore, consumptive behavior can be overcome by a guidance and counseling service, which is group guidance. This study used qualitative research using descriptive study results from interviews to some high school students. It was found from the results of interviews with high school students that students did not follow the consumptive behavior of today's era.